False Positive Tramadol Urine Testing in Patients Taking Fexofenadine: A Tale of Two Consecutive Cases - Yousuf, Suhair Mohammed; Alater, Ahmad Maaen; Alabdulla, Majid; Osman, Mugtaba (Case Reports in Psychiatry, 2023)
Urine drug screen immunoassays have been widely used as point-of-care testing for detection of various drug classes in substance use disorders. However, these immunoassays frequently result in false positive results. We report two patients that used 180 mg daily dose of fexofenadine hydrochloride for treatment of skin allergy and, falsely, tested positive for use of tramadol during urine drug screening. We recommend caution when interpreting positive tramadol urine screening among patients on fexofenadine treatment.